Bariatric surgery: techniques and mechanisms of action - Pories, Walter (Henry Stewart Talks, 2009)
Eastern North Carolina: an epidemiologic laboratory, The Development of the gastric bypass, Health effects of the gastric bypass, Potential mechanisms of action, Safety issues
Archived at 2021/02/25